1981
DOI: 10.1128/jb.148.1.30-42.1981
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the adenosine triphosphatase complex in Escherichia coli: assembly of F0 is dependent on the formation of specific F1 subunits

Abstract: A strain of Escherichia coli (AN1007) carrying the polar uncD436 allele which affects the operon coding for the F1-Fo adenosine triphosphatase (ATPase) complex was isolated and characterized. The uncD436 allele affected the two genes most distal to the operon promoter, i.e., uncD and uncC. Although the genes coding for the Fo portion of the ATPase complex were not affected in strains carrying this mutant allele, the lack of reconstitution of washed membranes by normal F1 ATPase suggested that a functional Fo m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Loo and Bragg (45) noted that a peptide, tentatively identified as the psi subunit, was missing from strain N144 membranes. The absence of psi would be consistent with the assembly model of Cox et al (7), which requires the presence of a and l for integration of this subunit. A better understanding of these and other complex mutants will require a more detailed analysis.…”
Section: Vol 156 1983supporting
confidence: 87%
“…Loo and Bragg (45) noted that a peptide, tentatively identified as the psi subunit, was missing from strain N144 membranes. The absence of psi would be consistent with the assembly model of Cox et al (7), which requires the presence of a and l for integration of this subunit. A better understanding of these and other complex mutants will require a more detailed analysis.…”
Section: Vol 156 1983supporting
confidence: 87%
“…However, further experimentation indicated that both the aand P-subunits of the F -ATPase were required for the assembly in vivo of the b-subunit into the Fo portion of the ATPase (Klionsky et al, 1983). Friedl et al (1983) also studied the integration of the b-subunit into the membrane by using various mutant strains and plasmid-bearing strains and, although they had some problems with proteolysis, reported data consistent with the assembly pathway previously reported by Cox et al (1981). However, Friedl et al (1983) also obtained some evidence for the membrane association of the bsubunit in the absence of other subunits.…”
Section: Discussionmentioning
confidence: 67%
“…The growth yields of all four strains were also similar (Table 2) and indicated that the partial-diploid strains had regained some capacity for oxidative phosphorylation as compared with the haploid controls. The ATPase activities (Table 2) of membrane preparations from these four strains also indicated that some assembly of the complete F1FO-ATPase had occurred compared with the interrupted assembly (Cox et al, 1981a) that occurs in the haploid strains.…”
Section: Effects Of Increased Gene Dosage Of the Unce408 Or Unce463 Amentioning
confidence: 89%